Use of an organic acid blend to control the spread of Salmonella Heidelberg and improve broiler performance - Sausen, Lourenço; Signor Mendes, Angélica; Refatti Sikorski, Rosana; Uliana, Rosiane de Fátima; Ferreira Zago, Cláudia Helena; Trevisan, Lucas Renato; Evangelista Guimarães, Bruno (Medicina Veterinária, 2022)
The objective was to evaluate an organic acid blend supplied via water and feed to control the spread of Salmonella Heidelberg in broilers from 1–31 days of age, and improve growth performance in broilers. The design was a complete randomized block with five treatments and five replicates, 25 experimental units (13 birds per unit, density of 13 birds/m2). A total of 325 one day old female chicks were randomly arranged in five treatments: T1 – Negative control (no acid blend via water and feed + 0.5 mL of physiological solution in water); T2 – Positive control (no acid blend via water and feed + inoculation of 0.5 mL of Salmonella Heidelberg (1.2 x 106 CFU); T3 – Acid blend via water + inoculation of 0.5 mL of Salmonella Heidelberg (1.2 x 106 CFU); T4 – Acid blend via feed + inoculation of 0.5 mL of Salmonella Heidelberg (1.2 x 106 CFU); T5 – Acid blend both via water and feed + inoculation of 0.5 mL of Salmonella Heidelberg (1.2 x 106 CFU) in drinking water and feed. The results were analyzed using Bayesian comparisons with 5% significance and a priori beta distribution. Significant effects of treatments were found on feed conversion at 21, 28, and 31 days, where treatments T3 and T5 had the best results. Regarding live weight, no significant effects were observed between treatments. There was no significant effect of using a mixture of organic acids in reducing the incidence of Salmonella Heidelberg among the treated groups, in intestines at nine days, using drag swab at 16 days, and crop collection at 31 days. There were no significant differences between the test groups and control groups.